THE ANALYSIS OF DISCOMFORT DURING PREGNANCY IN PUSKESMAS DARUL AMAN , THE DISTRICT OF ACEH TIMUR - Dewi, Ratna; Elizawati, Elizawati; Noviyanti, Noviyanti (Department of Midwifery, Health Polytechnic of Aceh, 2024)
Background: Pregnant women will experience physical and psychological changes that can cause discomfort. The discomforts during pregnancy include fatigue, vaginal discharge, cravings, frequent urination, nausea and vomiting, chloasma, hemorrhoids, constipation, shortness of breath, round ligament pain, dizziness, varicose veins in the legs and vulva, as well as gingivitis and epulis. Subjects and Method: The research method used is analytical with a cross-sectional approach. The sample in this study consists of 88 pregnant women, with the study conducted from January 5 to January 19, 2022—data analysis utilized univariate and bivariate methods with chi-square statistical testing. Results; The analysis of discomforts during pregnancy most frequently experienced by pregnant women includes urination with 80 respondents (90.9%), cravings with 79 respondents (89.8%), emesis gravidarum with 62 respondents (70.4%), and dizziness with 42 respondents (47.7%). Conclusion: There is a relationship between age and parity and physical and psychological discomfort during pregnancy.